The Effect of Free Cash Flow, Liquidity, and Firm Size on Financial Performance (Study on Transportation and Logistic Sector Listed on IDX) - Maulana, Zaky; Shiyammurti, Nastiti Rizky (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The transportation and logistics sector plays a vital role in supporting economic activities, however, it experienced significant operational and financial challenges in the post-COVID-19 period. This study aims to examine the effect of free cash flow, liquidity, and firm size on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange during 2020–2024. This research employs a quantitative approach using secondary data obtained from companies annual reports and financial statements. The purposive sampling technique was applied, resulting in 140 observations from 28 companies. The data were analyzed using panel data regression with the Common Effect Model (CEM). The findings indicate that free cash flow and liquidity have a positive and statistically significant effect on financial performance, whereas firm size has a positive but statistically insignificant effect. The results suggest that effective free cash flow management and maintenance of short term liquidity are critical factors in improving corporate profitability. Furthermore, efficient management of free cash flow and liquidity contributes more significantly to financial performance than merely possessing larger asset bases. The novelty of this study lies in its focus on post pandemic period and its application of panel data regression analysis to examine the determinants of financial performance in the transportation and logistics sector.